Metallic ferromagnetic films with magnetic damping under 1.4 × 10−3 - Aidan J. Lee (Nature Portfolio, 2017)
Owing to their conductivity, low-damping metallic ferromagnets are preferred to insulating ferromagnets in charge-based spintronic devices, but are not yet well developed. Here the authors achieve low magnetic damping in CoFe epitaxial films which is comparable to conventional insulating ferromagnetic YIG films.